Post-harvest losses of fruits and vegetables and prospects for use of solar energy for conservation of agricultural products in Benin - AMOUSSA HOUNKPATIN, WALIOU BODOURIN AYANDA; BODJRENOU, Sam F.; ADOUNKPE, GNONLONFOUN JULIEN; KANDJI, Kelly; KOUNOUHEWA, Basile; AHOUANNOU, CLÉMENT (My University, 2021)
This study aims to estimating the post-harvest losses of fruits and vegetables (F&V) in Benin and examining the possibility of using solar energy to improve their conservation and the preservation of their nutritional potential. Data were collected through literature review and investigations through F&V value chains in the different agricultural development poles (ADP) or agro-ecological zones of Benin. In different ADP, losses of almost all seasonal F&V have been estimated at more than 50% of production. The most important losses (at least 80% of the quantity produced) are recorded for tomatoes. The quantities of most produced F&V (pineapple, mango, Solanum leaves and tomato) lost, could have covered the annual needs of nearly four million children for vitamin A, more than 700,000 children for iron and more than 400,000 children for zinc. The use of solar energy could therefore be considered as a solution to either facilitate the sustainable conservation of food products or to produce energy for the operation of small processing units at the local level.
Keywords: Post-harvest losses; Fruits and vegetables; Food preservation; Solar drying; Benin